Simplified time‐dependent crack width prediction for fiber reinforced concrete flexural members. (17th March 2021) - Watts, Murray J.; Amin, Ali; Gilbert, Raymond I.; Kaufmann, Walter; Minelli, Fausto
Abstract: One of the main areas where it is generally accepted that fibers play a significant contribution in construction practice is in the control of cracking. The primary objective of the fibers is to traverse cracks after they nucleate. The fibers provide some post‐cracking resistance to the otherwise brittle concrete. Much of the research contained in the literature on the cracking behavior of fiber reinforced concrete (FRC) members has focused on instantaneous load scenarios, without much consideration for the long‐term behavior (i.e., for members which are subjected to a sustained service moment). This is mirrored in design standards where limited guidance is provided to engineers to predict and assess the long‐term serviceability performance of FRC members. This paper presents a simplified model, which may be suitable for design, that can reliably predict the cracking behavior, over time, of FRC members subjected to a sustained in‐service flexural load. Predictions of the proposed model are compared to both instantaneous and long‐term data available in the literature. Satisfactory correlation is observed.